Pengaruh peningkatan skill, motivasi diri, dan strategi penyediaan tenaga kerja terhadap peningkatan karir sdm dan produktivitas kerja sebagai variabel intervening - SUNDAY ADE SITORUS; AMRIL ANAS; WILLIAM PARLINDUNGAN SIHOMBING; SUNDAY ADE SITORUS (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
The purpose of this study was to determine the relationship between increasing skills, self-motivation and workforce supply strategies that directly and indirectly affect HR career development through work productivity as an intervening variable. This study only describes the effect of career advancement through skill improvement, HR self-motivation and labor supply strategies by the government that affect HR work productivity, where skill improvement, self-motivation and workforce provision are government programs to help improve career advancement through work productivity. . The novelty of this research is improving skills, self-motivation and strategies for providing manpower to increase HR careers and work productivity. The research method used in this research is descriptive quantitative research method using path analysis. Partially, only the skill improvement and self-motivation variables have a positive and significant effect on the work productivity variable and the HR career improvement variable. Meanwhile, simultaneously, the variables of increasing skill and self-motivation have a positive and significant effect on the work productivity variable through the HR career improvement variable as an intervening variable. With the increase in the skills possessed by HR, they will always motivate themselves to be better and can increase their competence, so that it will affect their ability to be productive, so as to be able to create work productivity of each individual which leads to increased employee performance.